Inside Back Cover: Optical Visualization and Spectroscopic Techniques for Probing Water Transport in a Polymer Electrolyte Fuel Cell (ChemElectroChem 10/2015). Issue 10 (30th September 2015) - Nishida, Kosuke
<x xml:space="preserve">Abstract</x> The Inside Back Cover picture demonstrate how water transport and gas flow mechanisms in polymer electrolyte fuel cells can be investigated by using optical visualization techniques and laser diagnostics. More details can be found in the Minireview by K. Nishida on page 1458 in Issue 10, 2015 (DOI: 10.1002/celc.201500135).